Gut microbiome composition and functionality impact the responsiveness to a dairy-based product containing galacto-oligosaccharides for improving sleep quality in adults - Kortman, G A M; Hester, E R; Schaafsma, A; Mulder, J; Mallee, L; Nauta, A (Beneficial microbes, 2024)
Sleep quality and duration can be impacted by diet, and has been linked to gut microbiota composition and function as the result of communication via the microbiota-gut-brain axis. As one strategy to improve sleep quality could be through the modulation of the gut microbiome, we assessed the effects of a dairy-based product containing whey protein, galacto-oligosaccharides, tryptophan, vitamins and minerals after a 3 weeks intervention on gut microbiota composition and (gut-brain related) functions on basis of 67 healthy subjects with moderate sleep disturbances. Associations of the gut microbiota with sleep quality and with response/non-response to the treatment were revealed by shotgun metagenomics sequencing of faecal DNA samples, and subsequent analyses of microbiota taxonomy and generic functionality. A database of manually curated Gut-Brain Modules (GBMs) was applied to analyse specific microbial functions/pathways that have the potential to interact with the brain. A moderate discriminating effect of the DP treatment on gut microbiota composition was revealed which could be mainly attributed to a decrease in Pseudomonas resinovorans, Flintibacter sp. KGM00164, Intestinimonas butyriciproducens, and Flavonifractor plautii. As interindividual variance in microbiota composition could have given rise to a heterogenous responsiveness of the subjects in the intervention group, we zoomed in on the differences between responders and non-responders. A significant difference in baseline microbiota composition between responders and non-responders was apparent, showing lower Bifidobacterium longum and Bifidobacterium adolescentis, and higher Faecalibacterium prausnitzii relative abundances in responders. The findings provide leads with respect to the effectiveness and potential underlying mechanisms of mode of action in sleep improvement that could support future nutritional interventions to aid sleep improvement.